A conceptual review on classification, extraction, bioactive potential and role of phytochemicals in human health - Prashant Anil Pawase; Chetna Goswami; Rafeeya Shams; Vinay Kumar Pandey; Anjali Tripathi; Sarvesh Rustagi; Darshan G (Future Foods, 2024)
Natural substances present in plants called phytochemicals are essential for fostering favourable human health outcomes. These bioactive compounds support general health via a variety of processes. Phytochemicals have strong antioxidant qualities that aid in scavenging dangerous free radicals from the body. This antioxidant activity can promote cellular health by lowering oxidative stress, a major contributor to ageing and the onset of chronic diseases. Phytochemicals exhibit a dosage-dependent effect, which can either have beneficial or detrimental health outcome. Several in vivo and vitro studies have been conducted that strongly supports the health-promoting properties of phytochemicals in human diets. A diet that is rich in phytochemicals derived from fruits, vegetables, nuts, legumes, and whole grains has been linked to a lower incidence of lipid peroxidation, cardiovascular disorders, cancer, and other illnesses. Compounds such as β-glucans and echinacea stimulate immune responses, enhancing the body's ability to defend against infections and diseases. The study of phytochemicals has expanded the understanding of the biochemical diversity of plants and their potential applications in various fields of human life, including food and nutrition, pharmaceuticals, cosmetics, and agriculture. This review deals with the significance and varieties of phytochemicals used to enhance human nutrition and overall health.